The Influence Of Board Of Directors' Components On Social Responsibility Reputation In Lq-45 Index Companies - Atika Wulandari; Santi Yopie (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The aims of this study is to examine the effect of the diversity of the board director components on companies that have social responsibility (CSR) due to limited evidence that the diversity of the board of directors within a company affects the reputation of organizations or companies that are involved in social responsibility (CSR). The object of this study is a company listed on the LQ45 Index, which is a stock market index on the Indonesia Stock Exchange which consists of 45 companies that are included in the top 60 companies with the highest market capitalization in the past year. The diversity is based on gender diversity, board meetings, board education variety, board average age, and number of board of commissioners. There are 225 observation samples from 2017-2021. In this study it was concluded that the diversity of directors based on the matters mentioned above had a significant and positive impact. The diversity of components of a company's board of directors influences an organization or company in decision making and involvement in social responsibility as demanded by directors or stakeholders. This study aims to determine the importance of the diversity of the board directors on social responsibility and the positive influence of the diversity of the board of directors in managing corporate social responsibility.